Volume equations for Scots pine trees in Kastamonu region - Dilara Nur Zaifoğlu; Fadime Sağlam (Turkish Journal of Forestry)
The objective of this study is to develop tree volume equations for Scots pine trees in the Kastamonu region and to compare the prediction capability of these equations with existing tree volume equations. For this purpose, stump diameter, diameter at breast height, diameters in each meter up to the top of the tree, and tree height measurements were measured on 127 sample trees from the Kastamonu Forest Enterprise in the Kastamonu Regional Directorate of Forestry. Subsequently, tree volumes were calculated based on these measurements and using the sectional method. This method entailed volumizing the trees in three sections: the stump section, the top section and the one-meter sections between the stump and the top sections. To develop single- and double-entry tree volume equations, the parameters of eight volume equations were estimated. Four statistical criteria were employed to identify the best predictive models. The coefficients of determination for the best predictive single- and double-entry models were found to be 0.972 and 0.975, respectively. Additionally, the results of these models were compared with the volume predictions derived from four models presented in the literature. The results of this study will enhance the accuracy of tree volume estimation for Scots pine stands in the Kastamonu region.